Multiple sclerosis management during the COVID-19 pandemic. (September 2020) - Moss, Brandon P; Mahajan, Kedar R; Bermel, Robert A; Hellisz, Kelsey; Hua, Le H; Hudec, Timothy; Husak, Scott; McGinley, Marisa P; Ontaneda, Daniel; Wang, Zhini; Weber, Malory; Tagliani, Paula; et al.
Background: People with multiple sclerosis (MS) may be at higher risk for complications from the 2019 coronavirus (COVID-19) pandemic due to use of immunomodulatory disease modifying therapies (DMTs) and greater need for medical services. Objectives: To evaluate risk factors for COVID-19 susceptibility and describe the pandemic's impact on healthcare delivery. Methods: Surveys sent to MS patients at Cleveland Clinic, Johns Hopkins, and Vall d'Hebron-Centre d'Esclerosi Múltiple de Catalunya in April and May 2020 collected information about comorbidities, DMTs, exposures, COVID-19 testing/outcomes, health behaviors, and disruptions to MS care. Results: There were 3028/10, 816 responders. Suspected or confirmed COVID-19 cases were more likely to have a known COVID-19 contact (odds ratio (OR): 4.38; 95% confidence interval (CI): 1.04, 18.54). In multivariable-adjusted models, people who were younger, had to work on site, had a lower education level, and resided in socioeconomically disadvantaged areas were less likely to follow social distancing guidelines. 4.4% reported changes to therapy plans, primarily delays in infusions, and 15.5% a disruption to rehabilitative services. Conclusion: Younger people with lower socioeconomic status required to work on site may be at higher exposure risk and are potential targets for educational intervention and work restrictions to limit exposure. Providers should be mindful of potential infusion delays and MS care disruption.